Functional Electrical Stimulation and the Modulation of the Axon Regeneration Program - Jara, Juan Sebastián; Agger, Sydney; Hollis, Edmund R. (Frontiers in Cell and Developmental Biology, 2020)
Neural injury in mammals often leads to persistent functional deficits as spontaneous repair in the peripheral nervous system (PNS) is often incomplete, while endogenous repair mechanisms in the central nervous system (CNS) are negligible. Peripheral axotomy elicits growth-associated gne programs in sensory and motor neurons that can support reinnervation of peripheral targets given sufficient levels of debris clearance and proximity to nerve targets. In contrast, while damaged CNS circuitry can undergo a limited amount of sprouting and reorganization, this innate plasticity does not re-establish the original connectivity. The utility of novel CNS circuitry will depend on effective connectivity and appropriate training to strengthen these circuits. One method of enhancing novel circuit connectivity is through the use of electrical stimulation, which supports axon growth in both central and peripheral neurons. This review will focus on the effects of CNS and PNS electrical stimulation in activating axon growth-associated gene programs and supporting the recovery of motor and sensory circuits. Electrical stimulation-mediated neuroplasticity represents a therapeutically viable approach to support neural repair and recovery. Development of appropriate clinical strategies employing electrical stimulation will depend upon determining the underlying mechanisms of activity-dependent axon regeneration and the heterogeneity of neuronal subtype responses to stimulation.